Diamond on aluminum nitride as a platform for integrated photonic circuits. Issue 8 (15th June 2016) - Gruhler, Nico; Yoshikawa, Taro; Rath, Patrik; Lewes‐Malandrakis, Georgia; Schmidhammer, Edgar; Nebel, Christoph; Pernice, Wolfram H. P.
Abstract : Diamond offers superior material properties for realizing advanced integrated optical components. Particularly attractive is its wide transparency window which covers visible and infrared wavelengths. To take advantage of the potential for broadband waveguiding, diamond needs to be surrounded by broadband transparent cladding materials. Here we use diamond deposited onto aluminum nitride as a platform for integrated optics. We demonstrate essential photonic circuitry for coupling light into on‐chip waveguides and show transmission both in the near‐infrared and visible wavelength range. Our approach holds promise for functional diamond devices that cover spectral regions up to the mid‐infrared. Left: Scanning electron micrograph of a diamond waveguide with an overlay of the mode profile. Right: material stack consisting of polycrystalline diamond (PCD) on aluminum nitride (AlN) on silicon (Si) (not to scale).